Մի հայկական մասունք միջնադարյան արաբական պոեզիայում - Ալբերտ Մուշեղյան (ՀՀ ԳԱԱ հրատ.)
Героем бунтарско-философской поэмы Аветика Исаакяна "Абу-Лала Маари" (1909г.) стал арабский поэт Абул-Ала ал Маари (973— 1057), автор медитативно-философских стихов и двустиший рационалистического направления. The Arab poet Abul-Ala al Mahari (937-1057), the author of meditative-philosophic poems and verses of rationalistic inclination, was so close spiritually to the Armenian poet Avetik Isahakian, that the latter chose him as his protagonist in his rebellious philosophical poem "Abu-Lala Mahari" (1909).
Keywords: Literature; Language and Literature